Isolation and identification of cyclic polyketides from Endiandra kingiana gamble (lauraceae), as BCL-XL/BAK and MCL-1/BID dual inhibitors, and approaches toward the synthesis of kingianins / Mohamad Nurul Azmi Mohamad Taib - Mohamad Nurul Azmi , Mohamad Taib (2015)
The preliminary screening showed that the bark of Endiandra kingiana Gamble exhibited potency as a modulating agent between Bcl-xL and Bak, which prompted its chemical investigation. Two groups of compounds were isolated and characterized; the endiandric acid series and the kingianin series. Eight new endiandric acid analogues (kingianic acids A-H [120-127]) and three new kingianin analogues (kingianin O-Q [128-130]) were isolated and structurally elucidated. The isolated compounds were evaluated for two bioassays; Bcl-xL/Bak and Mcl-1/Bid of binding affinities and cytotoxic effects against various human tumour cells. The second part describes the progression towards the total synthesis of kingianin analogues. The pentacyclic kingianin skeleton was formed by Diels-Alder reaction between two monomers having a bicyclo[4.2.0]octadiene backbone formed by a stereospecific electrocyclization of polyenes. The research was focusing on construction of bicyclo[4.2.0]octadiene monomer using [2+2] ketene cycloaddition approach at the early stage of the synthesis. One of the main advantages of such a strategy is the rapid assembly of the carbon skeleton of kingianins, thus maximizing the chances for good overall yields of the final products. So far, an efficient synthesis of the bicyclo[4.2.0]octene backbone was successfully achieved. Five approaches to synthesize this backbone starting from [2+2] cycloaddition of the cyclohexadienes to functionalized ketenes followed by functionalization of substituent at C-7 and C-8 positions with the correct relative configuration were described. From these approaches, compounds 280 and 311 were identified as the key intermediates. This key step of the synthesis provided an access to the kingianins skeleton.